A SURVEY ON CHATGPT USAGE PATTERNS AS A TOOL FOR READING COMPREHENSION OF ENGLISH STUDY PROGRAM STUDENTS FKIP UNRI - Puspita Sari, Desti; Azhar, Fadly; Mahdum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of artificial intelligence has introduced new digital tools that support learning activities, including in the field of language education. One of the most widely used AI tools is ChatGPT, which provides interactive assistance for various academic tasks. This study aims to investigate the usage patterns of ChatGPT as a tool to support reading comprehension among students of the English Study Program at the Faculty of Teacher Training and Education, Universitas Riau. The research employed a quantitative survey design to explore how students utilize ChatGPT in their reading activities. Data were collected through a questionnaire distributed to students to identify the frequency of use, purposes of use, and students’ perceptions regarding the effectiveness of ChatGPT in assisting reading comprehension. The findings indicate that many students frequently use ChatGPT to help them understand unfamiliar vocabulary, summarize texts, identify main ideas, and clarify complex sentences in English reading materials. In addition, students reported that ChatGPT helps them process information more efficiently and improves their overall understanding of academic texts. The results also reveal that students perceive ChatGPT as a practical and accessible learning support tool that enhances independent learning. However, the study also highlights the importance of using AI tools responsibly to avoid overreliance on technology in the learning process. Overall, this study suggests that ChatGPT can serve as a supportive digital resource for improving students’ reading comprehension skills in higher education contexts.